Soil, Water, and Land Use: I. Understanding Pesticide Interaction - Angela Schipper; Alison Edgell; Art Hornsby; Ron Jessup (EDIS)
Produced jointly by the Soil and Water Science Department and the 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and AgriculturalSciences. University of Florida, Revised March 1997; reviewed June 2002.